2018
DOI: 10.1017/s1751731118001957
|View full text |Cite
|
Sign up to set email alerts
|

Review: The compositional variation of the rumen microbiome and its effect on host performance and methane emission

Abstract: The rumen microbiome has the important task of supplying ruminants with most of their dietary requirements and is responsible for up to 90% of their metabolic needs. This tremendous feat is possible due to the large diversity of microorganisms in the rumen. The rumen is considered one of the most diverse ecosystems on the planet in terms of species diversity and functional richness. From the moment the feed is ingested, it enters a vast cascade in which specialized microorganisms degrade specific components of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 120 publications
(156 reference statements)
1
41
1
2
Order By: Relevance
“…Weimer [ 11 ] reported that rumen microbiomes exhibit remarkable specificity and resilience within hosts. Most attempts at introducing probiotics to rumens have resulted in only a temporary change after days or a few weeks, suggesting high host-specificity of rumen microbiome composition once established [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Weimer [ 11 ] reported that rumen microbiomes exhibit remarkable specificity and resilience within hosts. Most attempts at introducing probiotics to rumens have resulted in only a temporary change after days or a few weeks, suggesting high host-specificity of rumen microbiome composition once established [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both preweaning calves and mature animals have a Methanobacteriales order, but rumen of preweaning calves contains two additional orders, Methanosarcinales and Methanomicrobiales (41). The compositional variations in rumen archaea lead to shifts in substrate utilization, methanogenic pathway, and extent of CH 4 production (42).…”
Section: Ontogenesis Of the Rumen And Initial Microbial Colonizationmentioning
confidence: 99%
“…The rumen in animals is inhabited by the diverse microbiome, including bacteria, protozoa, fungi, and archaea. Different factors like temperature (38)(39)(40)(41)(42) • C), pH (5.5-7), and redox potential (250-450 mV) regulated by saliva buffering provide a specific environment for degradation of cellulolytic plant material by microbes (1).…”
Section: Introductionmentioning
confidence: 99%
“…Among these contributors, the influence of diet on gut microbial population structure is well established 14 17 . Rumen bacterial species’ and functional composition of the rumen microbiota is an important factor that contributes towards animal performance and efficiency 18 . Additionally, studies in small ruminants have demonstrated the host mucosal innate immune function to affect rumen microbial community composition 19 .…”
Section: Introductionmentioning
confidence: 99%